Seasonal and vertical distribution of Meloidogyne hapla in organic soil - Bélair, G. (Phytoprotection, 1998)
The seasonal population fluctuations of the northern root-knot nematode Meloidogyne hapla on car rot (Daucus carota), onion (Allium cepa), and weeds were observed on organic soils in southwestern Quebec. Lowest population densities of M. hapla juveniles (J2) were recorded in July and August, followed by a peak in September and October in plots with carrot or weedy fallow. In onion, J2 densities remained near or below the detectable level during most of the sampling period, but a small trend in population increase was also detected in the fall. The vertical distribution of M. hapla was similar in carrot weedy fallow, and onion plots. J2 were regularly recovered from the four sampling depths (0-10,11-20, 21-30, and 31-40 cm). The numbers of J2 were greater in the 0-20 cm depth than the 21-40 cm depth, with 67, 68, and 60% of the total M. hapla population in the 0-20 strata for carrot, weedy fallow, and onion, respectively. The tomato bioassay method was more sensitive than the Baermann pan method for detecting low M. hapla densities. Because of the poor correlation between J2 densities in the soil and the number of galls on tomato roots in the bioassay, a measurement of J2 abundance such as the Baermann pan method shoud be supported by bioassay to further assist growers in their decision process for the management of M. hapla in organic soil.